Pengembangan Bahan Ajar Hikayat Berbantuan Media Renderforest untuk Meningkatkan HOTS Siswa Kelas X SMK Negeri 1 Patumbak - Batubara, Khairunnisa; Andriany, Liesna; Kartika, Rika (Medan Resource Center, 2024)
This study aimed to develop folklore teaching materials (sagas/hikayat) assisted by Renderforest media to improve the thinking skills of students in class X PPLG 1, X PPLG 2, and X BDP 1 at SMK Negeri 1 Patumbak. Using a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), data were collected through observations and questionnaires. The results showed that the teaching materials for folk tales (saga) assisted by Renderforest media were rated